Predictors of Osteoporosis Preventive Behaviors among Women: An Application of the Transtheoretical Model - Sajad Etehadnezhad; Zahra Moradi; Mansour Kashfi; Ali Khani-jeihooni; Zahra Khiyali (Hamadan University of Medical Sciences, 2018)
Background and Objectives: Behavioral change is one of the most powerful strategies for preventing osteoporosis. The aim of this study was to investigate the osteoporosis preventive behaviors in women based on the transtheoretical model. Materials and Methods: This cross sectional descriptive-analytical study was performed on 400 women over 30 years covered by Fasa health care centers in 2018 that were selected by simple random sampling. The instruments of data collection included a personal information questionnaire, awareness, change stages, decision-making balance, self-efficacy in two parts of physical activity and dietary calcium, and a calcium intake questionnaire, as well as a checklist for physical activity and calcium intake performance. The data were analyzed by SPSS 22 software, using Pearson correlation coefficient, Chi-square, independent t-test, and multiple regression analysis. Results: The majority of the participants were involved with calcium intake performance (41.25%) and walking (46.25%) at the precontemplation stage. There was a direct correlation between calcium intake performance and self-efficacy of calcium intake (p=0.032; r=0.125) and an inverse correlation with perceived barriers of calcium intake (p=0.045; r=-0.187). There was a direct correlation between walking performance with exercise benefits (p=0.020; r=0.128) and exercise self-efficacy (p=0.032; r=0.184), and a reverse correlation with perceived barriers of exercise (p=0.040; r=-0.102). Totally, the variables under the study predicted 28.6% of the variance in walking and 30.2% of the variance in calcium intake behavior. Conclusion: Transtheoretical model structures can predict osteoporosis preventive behaviors in women. The predictive power of self-efficacy for walking behavior and calcium intake is more than other structures.